Hubungan mekanisme koping orang tua dengan dampak hospitalisasi pasca operasi pada anak prasekolah di Ruang Rawat Inap Raudhah 2 BLUD RSU dr. Zainoel Abidin Banda Aceh - Nurhayati Nurhayati; Lia Wahyuna (Jurnal SAGO Gizi dan Kesehatan, 2021)
Background: Preschool is when children like to imagine and begin to build control of body systems. When preschool children experience hospitalization, activities will be limited so that children will lose their strength. When a child is hospitalized, parental support is very influential in minimizing the impact of hospitalization.Objectives: This study examines the relationship between parental coping mechanisms and the impact of postoperative hospitalization on preschool children in the Raudhah 2 inpatient room.Methods: This research method uses a correlational design with a cross-sectional study approach. The study was conducted at the Zainoel Abidin Hospital in Banda Aceh, 2018. The sample was taken by purposive sampling with a total of 38 respondents. Coping aspect data was collected using a questionnaire with a Gutman scale and the postoperative hospitalization impact variable using a Likert scale, and then interviews were conducted. Processing is done in stages, starting from editing, coding, tabulating, and cleaning. Data were analyzed using the Chi-Square test at 95% CI.Results: There was a relationship between parental coping focused on emotion (p= 0.005) and problem-focused coping (p= 0.028) with the impact of postoperative hospitalization on preschool children. In addition, parental coping mechanisms have a significant relationship (p < 0.05) with the effect of postoperative hospitalization on preschool children in the Raudhah 2 RSUZA inpatient ward, with p-value = 0.001.Conclusion: There is a significant relationship between parental coping mechanisms and the impact of postoperative hospitalization on preschool children in the Raudhah 2 inpatient room at RSU dr. Zainoel Abidin.